The socio-economic effects of Karun 3 dam on the sustainable development of rural areas. A case study in Iran - Hojat Allah Sadeghi; Seyed skandar Seidaiy; Mohammad Reza Rezvani (Human Geographies: Journal of Studies and Research in Human Geography, 2017)
Aiming to explain the socio-economic effects of reservoir dams on the sustainable development of rural areas, this paper, as a case study on Iran focuses on Karun 3 Dam, the largest arch dam of the Middle East. 350 rural household were studied through survey data collection. The households settled in 38 villages where questionnaires were distributed accordingly. The results showed that the dam has been effective in improving agriculture and boosting local economic indices, but has not affected on tourism, industrial development and employment. Also, it seems that the indices of quality of life, welfare and social capital correlate with inefficient dam performance in rural sustainable economic development. Evaluation of the effective social and economic variables of the dam in relation to the sustainable development of rural settlements shows that there is a duality in management based sustainable development that has prevented the positive effects of the dam on villages.